2021
DOI: 10.1002/bkcs.12429
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in ensemble density functional theory and linear response theory for strong correlation

Abstract: The formulations and performances of spin-restricted ensemble-referenced KS and mixed-reference spin-flip time-dependent density functional theory incorporating strong correlations into density functional theories are documented. As a result of balanced dynamic and nondynamic correlation, they are capable of describing strongly correlated challenging systems including diradicals, bond dissociation, conical intersections, doubly excited states, and so on, overcoming the limitations of current density functional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 166 publications
0
17
0
Order By: Relevance
“…In contrast, the recently developed mixed-reference spin-flip time-dependent density functional theory (MRSF-TDDFT, MRSF for brevity) [10][11][12] properly described not only CI 10 8 but also CI 21 s, 9 in satisfactory agreement with the results of EOMCC as well as multi-state many-body perturbation theory, such as XMS-CASPT2.…”
Section: Introductionmentioning
confidence: 88%
“…In contrast, the recently developed mixed-reference spin-flip time-dependent density functional theory (MRSF-TDDFT, MRSF for brevity) [10][11][12] properly described not only CI 10 8 but also CI 21 s, 9 in satisfactory agreement with the results of EOMCC as well as multi-state many-body perturbation theory, such as XMS-CASPT2.…”
Section: Introductionmentioning
confidence: 88%
“…This allows MRSF-TDDFT to overcome the major limitations of conventional TDDFT without the spin-contamination pitfalls of spin flip (SF)-TDDFT, 32 while faithfully reproducing the results of the much more expensive ab initio wave function theories. 29 In a series of studies, 30,31,[33][34][35][36][37][38][39][40][41] it has been demonstrated that the MRSF-TDDFT approach can also yield accurate nonadiabatic coupling matrix elements (NACMEs), 33,35 enabling reliable non-adiabatic molecular dynamics (NAMD) simulations, 40 a topologically correct description of conical intersections, 30,36,39 and accurate values of singlet-triplet gaps. 31,34 In the current letter, by combining standard techniques such as MOM for building a CHP reference and REW for computing X-ray states, we demonstrate that the MRSF-TDDFT is a practical, efficient and very accurate protocol in the computations of X-ray spectroscopy without any major methodological restrictions.…”
Section: Toc Graphicmentioning
confidence: 99%
“…In this regard, LR theories are still preferable for their practicality and generality and could be advantageous for an accurate description of X-ray spectroscopy if orbital relaxation effects are included . In this article, we propose the use of the recently developed mixed-reference spin-flip (MRSF)–TDDFT (MRSF for brevity in some places) as an accurate and general strategy for X-ray spectroscopy. Unlike TDDFT formalism, the major challenges of conventional LR theories mentioned above can be rather easily overcome by MRSF. It needs to be first clarified that the commonly adopted core-hole relaxation with an ionic system by removing one electron does not represent the lowest-energy XAS states.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a separate series of studies, it has been demonstrated that the MRSF-TDDFT approach can also yield accurate nonadiabatic coupling matrix elements (NACMEs), , enabling reliable NAMD simulations, a topologically correct description of conical intersections, , and accurate values of singlet–triplet gaps. , Thus, the MRSF-TDDFT methodology overcomes the major limitations of conventional TDDFT , and avoids the spin-contamination pitfalls of SF-TDDFT, , while providing an accurate low-cost computational protocol for simulating photochemistry involving IC phenomena, capable of faithfully reproducing the results of the much more expensive, state-of-the-art, ab initio wave function calculations.…”
Section: Theory and Computational Detailsmentioning
confidence: 99%